Role of metabolic conditions in cardiorenal diseases: initiating pathways and therapeutic targeting - Wu, Yeshun; Xu, Hongqing; Tu, Xiaoming; Gao, Zhenyan (Frontiers in Nutrition, 2025)
Albuminuria, a core indicator of kidney injury, is closely associated with cardiovascular disease prognosis. Through multiple mechanisms, metabolic abnormalities, such as hyperglycemia, hyperuricemia, obesity, and dyslipidemia, contribute to the onset and progression of albuminuria and significantly increase the risk of adverse cardiovascular outcomes. Based on recent clinical studies and basic experimental evidence, this review systematically elucidates how metabolic conditions are involved in the relationship between albuminuria and cardiac prognosis, encompassing several mechanisms, including chronic inflammation, endoplasmic reticulum stress, renin–angiotensin–aldosterone system overactivation, hemodynamic alterations, vascular endothelial dysfunction, mitochondrial dysfunction, and lipotoxicity. Additionally, it explores clinical intervention strategies. This review underscores the pivotal role of metabolic conditions in driving cardiorenal diseases and outlines evidence-based strategies for clinical management.